Mechanically Recoverable and Highly Efficient Perovskite Solar Cells: Investigation of Intrinsic Flexibility of Organic–Inorganic Perovskite. Issue 22 (24th September 2015) - Park, Minwoo; Kim, Hae Jin; Jeong, Inyoung; Lee, Jinwoo; Lee, Hyungsuk; Son, Hae Jung; Kim, Dae‐Eun; Ko, Min Jae
Abstract : Highly efficient solar cells with sustainable performance under severe mechanical deformations are in great demand for future wearable power supply devices. In this regard, numerous studies have progressed to implement flexible architecture to high‐performance devices such as perovskite solar cells. However, the absence of suitable flexible and stretchable materials has been a great obstacle in the replacement of largely utilized transparent conducting oxides that are limited in flexibility. Here, a shape recoverable polymer, Noland Optical Adhesive 63, is utilized as a substrate of perovskite solar cell to enable complete shape recovery of the device upon sub‐millimeter bending radii. The employment of stretchable electrodes prevents mechanical damage of the perovskite layer. Before and after bending at a radius of 1 mm, power conversion efficiency (PCE) is measured to be 10.75% and 10.4%, respectively. Additionally, the shape recoverable device demonstrates a PCE of 6.07% after crumpling. The mechanical properties of all the layers are characterized by nanoindentation. Finite element analysis reveals that the outstanding flexibility of the perovskite layer enables small plastic strain distribution on the deformed device. These results clearly demonstrated that this device has great potential to be utilized in stretchable power supply applications. Abstract : Indium tin oxide‐free and shape‐recoverable perovskite solar cells with a high‐power conversion efficiency (PCE = 10.83%) and an excellent mechanical durability (PCE = 9.68% after 1000 bending cycle at r = 1 mm bending radius) is demonstrated. The mechanical behavior of intrinsically flexible and stretchable perovskite layer is thoroughly investigated by nanoindentation measurements and finite element analysis.